2008
DOI: 10.1111/j.1756-185x.2008.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution ultrasonographic diagnosis of plantar fasciitis: a correlation of ultrasound and magnetic resonance imaging

Abstract: Aim and Method:  In a prospective study of nine men and eight women with suspected unilateral or bilateral plantar fasciitis, 23 symptomatic heels were examined by both high‐resolution ultrasound and a preplanned limited sagittal magnetic resonance imaging (MRI) protocol to assess the different signs. Eleven healthy volunteers (22 heels) acted as controls. Results:  The plantar fascia was thickened in symptomatic feet. The thickness of the plantar fascia in symptomatic feet was (3.0–7.0 mm; 4.9 ± 1.3) measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
(43 reference statements)
0
8
0
Order By: Relevance
“… Karabay et al (2007) reported that the average thickness of the plantar fascia of patients with plantar fasciitis was approximately 4.8 mm. Abdel-Wahab et al (2008) reported a similar result, saying that the plantar fascia thickness was about 4.9 mm among patients with plantar fasciitis. Other previous studies reported the average fascia thickness of patients with plantar fasciitis to be around 5.2–5.9 mm ( Cardinal et al, 1996 ; Gibbon and Long, 1997 ; Kane et al, 2001 ).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“… Karabay et al (2007) reported that the average thickness of the plantar fascia of patients with plantar fasciitis was approximately 4.8 mm. Abdel-Wahab et al (2008) reported a similar result, saying that the plantar fascia thickness was about 4.9 mm among patients with plantar fasciitis. Other previous studies reported the average fascia thickness of patients with plantar fasciitis to be around 5.2–5.9 mm ( Cardinal et al, 1996 ; Gibbon and Long, 1997 ; Kane et al, 2001 ).…”
Section: Discussionmentioning
confidence: 63%
“…For the ultrasonic image, the subject was in a prone position and made a knee extension with 90° flexion of the ankle. After vertically scanning the proximal interior where the plantar fascia is attached to the surface of the calcaneus, we measured the thickness of the plantar fascia on the node area of the calcaneus, where the plantar fascia originates ( Abdel-Wahab et al, 2008 ; Radwan et al, 2016 ) ( Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-one studies described the association between PFT and PF,27 29 32 34 39 40 43 44 47 49 53 59–68 nine of which applied matching for possible confounding factors such as age, gender and body weight (see online supplementary file 2) 34 40 44 47 49 60 62 63 66…”
Section: Imaging Factorsmentioning
confidence: 99%
“…Pooled data for all imaging techniques from 19 studies showed that people with PF had an average 2.32 mm (95% CI 1.86 to 2.79) thicker plantar fascia compared to control participants (MD of (figure 5). 27 29 32 34 39 40 43 44 49 59–68 Subgroup analyses for the separate imaging techniques showed a MD of 2.20 (95% CI 1.68 to 2.72) for US, 3.36 (95% CI 1.81 to 4.90) for MRI and 2.40 (95% CI 1.88 to 2.92) for X-ray. Similar trends were seen in the two studies in which pooling was not possible 47 53.…”
Section: Imaging Factorsmentioning
confidence: 99%
“…PF is a multifactorial and self-limiting disorder that several factors are involved in its onset [22]. Common risk factors usually reported in the literature include aging; high body mass index; anatomical problems such as pes planus, pes cavus foot types, excessive tibial torsion, or leg length discrepancy; tightness in gastrocnemius and soleus muscles; weakness of intrinsic foot muscles; prolonged standing and running activities; using improper shoe fit and wear; previous injury and running variables such as surface, speed, frequency and distance per week [20,[23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%